Early Pro-Inflammatory Signal and T-Cell Activation Associate With Vaccine-Induced Anti-Vaccinia Protective Neutralizing Antibodies - Hou, Jue; Wang, Shuhui; Li, Dan; Carpp, Lindsay N.; Zhang, Tong; Liu, Ying; Jia, Manxue; Peng, Hong; Liu, Chang; Wu, Hao; Huang, Yunda; Shao, Yiming (Frontiers in Immunology, 2021)
Both vaccine “take” and neutralizing antibody (nAb) titer are historical correlates for vaccine-induced smallpox protection. We analyzed a subset of samples from a phase 2a trial of three DNA/HIV-1 primes and a recombinant Tiantan vaccinia virus-vectored (rTV)/ HIV-1 boost and found that a proportion of participants showed no anti-vaccinia neutralizing antibody (nAb) response to the rTV/HIV-1 boost, despite successful vaccine “take”. Using a rich transcriptomic and vaccinia-specific immunological dataset with fine kinetic sampling, we investigated the molecular mechanisms underlying nAb response. Blood transcription module analysis revealed downregulation of the AP-1 pathway in responders but not non-responders, as well as upregulation of T cell-activation in responders. Furthermore, transcriptional factor network reconstruction revealed upregulation of AP-1 core genes at Hour 4 and Day 1 post rTV/HIV-1 vaccination followed by downregulation from Day 3 until Day 28 in responders. In contrast, AP-1 core and pro-inflammatory genes were upregulated at Day 7 in non-responders. We speculate that persistent pro-inflammatory signaling early post rTV/HIV-1 vaccination inhibits the nAb response.